Prescribing sodium-glucose co-transporter-2 inhibitors for type 2 diabetes in primary care: influence of renal function and heart failure diagnosis - Hinton, W; Feher, MD; Munro, N; Joy, M; de Lusignan, S (BioMed Central, 2021)
Background Sodium-glucose co-transporter-2 inhibitors (SGLT-2is) are licenced for initiation for glucose lowering in people with type 2 diabetes (T2DM) with an estimated glomerular filtration rate (eGFR) ≥ 60 mL/min/1.73m2). However, recent trial data have shown that these medications have renal and cardio-protective effects, even for impaired kidney function. The extent to which trial evidence and updated guidelines have influenced real-world prescribing of SGLT-2is is not known, particularly with co-administration of diuretics. Methods We performed a cross-sectional analysis of people with T2DM registered with practices in the Oxford-Royal College of General Practitioners (RCGP) Research and Surveillance Centre (RSC) database on the 31st July 2019. We calculated the percentage of people prescribed SGLT-2is according to eGFR categories (< 45, 45–59, and ≥ 60 mL/min/1.73m2), with a heart failure diagnosis and stratified by body mass index categories (underweight, normal weight, overweight, obese), and with concomitant prescription of a diuretic. Multilevel logistic regression analysis was performed to determine whether heart failure diagnosis and renal function were associated with SGLT-2i prescribing. Results From a population of 242,624 people with T2DM across 419 practices, 11.0% (n = 26,700) had been prescribed SGLT-2is. The majority of people initiated SGLT-2is had an eGFR ≥ 60 mL/min/1.73m2 (93.2%), and 4.3% had a heart failure diagnosis. 9,226 (3.8%) people were prescribed SGLT-2is as an add-on to their diuretic prescription. People in the highest eGFR category (≥ 60 mL/min/1.73m2) were more likely to be prescribed SGLT-2is than those in eGFR lower categories. Overweight (OR 2.05, 95% CI 1.841–2.274) and obese people (OR 3.84, 95% CI 3.472–4.250) were also more likely to be prescribed these medications, whilst use of diuretics (OR 0.74, 95% CI 0.682–0.804) and heart failure (OR 0.81, 95% CI 0.653–0.998) were associated with lower odds of being prescribed SGLT-2is. Conclusions Prescribing patterns of SGLT-2is for glucose lowering in T2DM in primary care generally concur with licenced indications according to recommended renal thresholds. A small percentage of people with heart failure were prescribed SGLT-2is for T2DM. An updated analysis is merited should UK National Institute for Health Care and Excellence prescribing guidelines for T2DM be revised to incorporate new data on the benefits for those with reduced renal function or with heart failure.